2022
DOI: 10.1371/journal.pgen.1009963
|View full text |Cite
|
Sign up to set email alerts
|

Multi-insecticide resistant malaria vectors in the field remain susceptible to malathion, despite the presence of Ace1 point mutations

Abstract: Insecticide resistance in Anopheles mosquitoes is seriously threatening the success of insecticide-based malaria vector control. Surveillance of insecticide resistance in mosquito populations and identifying the underlying mechanisms enables optimisation of vector control strategies. Here, we investigated the molecular mechanisms of insecticide resistance in three Anopheles coluzzii field populations from southern Côte d’Ivoire, including Agboville, Dabou and Tiassalé. All three populations were resistant to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 78 publications
3
36
0
Order By: Relevance
“…All qPCR reactions, including the species identification, target-site and metabolic resistance assays, were performed on a Bio-Rad CFX 96 real-time PCR machine (Bio-Rad; Hercules, CA, USA). In each reaction, 1 µl of the nucleic acids extract from individual mosquitoes was added to the one-step reverse transcription qPCR (RT-qPCR) master mix supplied by Fast Track Diagnostics (Esch-sur-Alzette, Luxembourg) together with the primers and probes at the concentrations described by Wipf et al [30] to reach a total reaction volume of 10 µl. The following thermal cycle conditions were used for all assays: 50 °C for 15 min, 95 °C for 3 min, followed by 40 amplification cycles of 95 °C for 3 s and 60 °C for 30 s. The purified nucleic acids were subjected to two complementary TaqMan qPCR assays to identify the 141 specimens to species level within the An.…”
Section: Molecular Species Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…All qPCR reactions, including the species identification, target-site and metabolic resistance assays, were performed on a Bio-Rad CFX 96 real-time PCR machine (Bio-Rad; Hercules, CA, USA). In each reaction, 1 µl of the nucleic acids extract from individual mosquitoes was added to the one-step reverse transcription qPCR (RT-qPCR) master mix supplied by Fast Track Diagnostics (Esch-sur-Alzette, Luxembourg) together with the primers and probes at the concentrations described by Wipf et al [30] to reach a total reaction volume of 10 µl. The following thermal cycle conditions were used for all assays: 50 °C for 15 min, 95 °C for 3 min, followed by 40 amplification cycles of 95 °C for 3 s and 60 °C for 30 s. The purified nucleic acids were subjected to two complementary TaqMan qPCR assays to identify the 141 specimens to species level within the An.…”
Section: Molecular Species Identificationmentioning
confidence: 99%
“…The following thermal cycle conditions were used for all assays: 50 °C for 15 min, 95 °C for 3 min, followed by 40 amplification cycles of 95 °C for 3 s and 60 °C for 30 s. The purified nucleic acids were subjected to two complementary TaqMan qPCR assays to identify the 141 specimens to species level within the An. gambiae complex with previously described adaptations to the original protocols put forth by Wipf et al [30].…”
Section: Molecular Species Identificationmentioning
confidence: 99%
“…Several studies have shown a wide spread resistance in local Anopheles to most of the insecticide classes currently used in malaria vector control (e.g. pyrethroids, DDT and carbamates) [5][6][7][8]. The existence of multiple mechanisms of resistance in the main vector, Anopheles gambiae sensu lato (s.l.)…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, deltamethrin-resistant strains were susceptible to spinosad by ingestion and the spinosadresistant strain JW-100 s was susceptible to deltamethrin, indicating that spinosad is a good candidate for spray, when needed, in fields where bait stations with deltamethrin are deployed. Interestingly, negative cross-resistance between pyrethroid resistance mediated by P450 and organophosphates has been reported in mosquitoes (Wipf et al 2022). However, the only organophosphate approved for Medfly control in citrus crops in Spain is phosmet, whose use is very limited.…”
Section: Discussionmentioning
confidence: 99%